Leadership challenges to the Episcopacy in the Anglican Diocese of Harare in Post-Independent Zimbabwe : a pastoral theological perspective (1980-2013) - Meylahn, Johann-Albrecht (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2016.